Marginal zone lymphoma of palatine tonsil with prominent plasmacytic differentiation: A CARE-compliant article and review of literature. Issue 2 (January 2018) - Ma, Shuang; Jug, Rachel; Shen, Shuai; Zhang, Wan-Lin; Xu, Hong-Tao; Yang, Lian-He
Abstract: Rationale: The palatine tonsil is an important component of Waldeyer's ring and a site commonly involved by lymphoma. Interestingly, although it is a site of mucosa-associated lymphoid tissue (MALT), primary MALT lymphoma of the palatine tonsil is rare, especially with prominent plasmacytic differentiation. Patient concerns: A 59-year-old woman presented to the hospital with a 1-month history of odynophagia. The patient had no fever or pruritus during this period and she declared no family history of hematolymphoid malignancy. Diagnosis: Histopathological examination demonstrated effacement of tonsil architecture; normal follicles were replaced by plasmacytoid tumor cells and small lymphocytes. The tumor cells expanded the marginal zone and infiltrated interfollicular regions, as well as scattered residual follicles. Immunostaining showed tumor cells positive for cluster of differentiation (CD)20, CD79a, paired box-5, Mum 1, and B cell lymphoma (Bcl)-2, and negative for CD5, CD 23, cyclin D1, Bcl-6, and CD10. Staining for κ and λ showed prominent light chain restriction. The tumor was classified as tonsil MALT lymphoma with prominent plasmacytic differentiation. Interventions: After the patient was diagnosed with MALT lymphoma with prominent plasmacytic differentiation, she underwent complete surgical resection and radiotherapy. Outcomes: There was no recurrence evident at 6-months follow-up. Lessons: Primary tonsil MALT lymphoma with prominent plasmacytic differentiation is very rare and difficult to distinguish from other B-cell lymphomas with plasmacytoid morphology, such as follicular lymphoma, lymphoplasmacytic lymphoma, and chronic lymphocytic leukemia/small lymphocytic lymphoma. Accurate diagnosis of this entity is important in guiding therapy so as to avoid overtreatment.